What makes a good handover in a care home for older people?. Issue 3 (29th August 2019) - Moriarty, Jo; Norrie, Caroline; Manthorpe, Jill; Lipman, Valerie; Elaswarapu, Rekha
Abstract : Purpose: The purpose of this paper is to investigate the content, purpose and effectiveness of the handover of information between care home staff beginning and completing a shift. Design/methodology/approach: This was an exploratory study drawing on ethnographic methods. A total of 27 interviews with a range of care home staff, including managers, registered nurses, senior care workers and care workers were undertaken in five care homes selected to give a good contrast in terms of size, ownership, shift patterns and type of handover. Findings: Most handovers were short – lasting 15 min or so – and were held in the office or secluded area in which staff could talk privately. They lasted longer in one home in which the incoming and outgoing shifts physically visited each resident's room and the communal spaces. Staff felt that handovers were important for the efficient running of the home as well as to alert everyone to changes in a resident's health or important events, such as a hospital appointment. In one home, handheld devices enabled staff to follow a resident's care plan and update what was happening in real time. Research limitations/implications: This was a small scale study based on data from a limited number of care homes. Practical implications: The increasing popularity of 12 h shifts means that many homes only hold two short handovers early in the morning and in the evening when the night staff arrive. There appears to be a trend to reduce the number of staff paid to attend handover. Despite this, handovers remain an important component of the routine of a care home. The information contained in handover relates to the running of the care home, as well as residents' wellbeing, suggesting that, while their content overlaps with written records in the home, they are not superfluous. Originality/value: Although the literature on handovers in hospitals is extensive, this appears to be the first published study of handover practices in care homes.